SAT0109 Quantitative estimates of damage and distress, in addition to inflammation, and the proportion each of the 3 variables affects clinical management decisions (total=100%) may clarify assessment of clinical status in patients with rheumatoid arthritis (RA). (15th June 2017) - Gibson, KA; Castrejon, I; Pincus, T
Abstract : Background: Quantitative assessment in rheumatoid arthritis (RA) is directed to inflammatory activity (INF) and not to joint damage (DAM) and distress (STR - seen as fibromyalgia, depression, etc.). However, DAM and STR may affect clinical management and outcomes of treatment in many RA patients. For example, an RA patient with well-controlled INF who has secondary fibromyalgia may have 0 swollen joints (SJC) and an ESR≥ of 15, but nonetheless have a DAS28 of 5.1, CDAI of ≥22, and RAPID3 of ≥16 (indicating high activity), based on 14/28 tender joints and a patient global assessment of 80/100. Therefore, quantitative estimates of DAM, and STR, as well as INF may clarify patient status and clinical management decisions. Objectives: To analyze physician quantitative estimates for the proportion of management decisions attributed to INF, DAM, or STR (total=100%) in RA patients seen in routine care. Methods: At one academic rheumatology center, the rheumatologist completes four 0–10 visual analog scales (VAS) for overall global assessment (DOCGL), INF, DAM, and STR. In patients with DOCGL ≥2, the proportion of management decisions are estimated as %INF+%DAM+%STR=100%. Cross-tabulations were computed for various phenotypes in 5 INF+DAM and INF+STR categories, 0, 1–20%, 21–40%, 42–60%, and 61–100%. Results: Among the 77 RA patients, >40% of clinical management decisions were attributed to INF in only 31 (40%), versus >40% to DAM in 33 (43%), and >40% to STR in 17 (22%) (Table). No category of INF+DAM or INF+STR included more than 20% of the patients, and patients were found in 17 of 25 possible categories for combinations of INF+DAM and INF+STR. The 13 patients (17%) in whom INF was estimated to contribute 0% to management included 3 of 5 DAM and 5 of 5 STR categories (Table). The 23 patients with 1–20% of management attributed to INF included 4/5 DAM and 5/5 STR categories. The 10 with 21–40% INF included 4/5 DAM and 4 STR categories. The 16 with 41–60% attributed to INF included 3 DAM and 2 STR categories. Only 15 of the 77 patients (19%) had >60% attributed to INF. Conclusions: Quantitative physician estimates of the proportion of clinical management decisions attributed INF, DAM, and STR may help clarify RA patient status and document a basis for clinical decisions. High levels of DAM and/or STR may explain in part why a target of RA remission often is not met in many patients seen in routine clinical care. 1 References: Tymms et al, Arth Care & Res 66:190–196, 2014. Disclosure of Interest: K. Gibson: None declared, I. Castrejon: None declared, T. Pincus Shareholder of: Health Report Services, Inc